2019
DOI: 10.3390/pr7070429
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement and Energy Cost Reduction under Different Scenarios for a Parabolic Trough Solar Power Plant in the Middle-East Region

Abstract: Concentrated solar power (CSP) is a leading renewable energy technology, and the parabolic trough (PT) is one of the most used configurations of CSP. In the present study, the performance improvement and energy cost reduction of a 50 MWe PT plant for Abu Dhabi, United Arab Emirates (UAE) is presented. The simulations were carried out using the System Advisor Model software. The analyses of a PT plant with different technologies/parameters are undertaken in the first instance for seven cases. These cases includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Specifically, the LCOE of the PT Plant is much lower. Also, the LCOE of CSP plants for different locations in Pakistan is in good agreement with the LCOE of CSP plants available in the most recent literature [15,21,[33][34][35]. Thus, it can be concluded that the CSP plants in Pakistan are economically feasible/viable.…”
Section: Economic Analysessupporting
confidence: 84%
See 1 more Smart Citation
“…Specifically, the LCOE of the PT Plant is much lower. Also, the LCOE of CSP plants for different locations in Pakistan is in good agreement with the LCOE of CSP plants available in the most recent literature [15,21,[33][34][35]. Thus, it can be concluded that the CSP plants in Pakistan are economically feasible/viable.…”
Section: Economic Analysessupporting
confidence: 84%
“…Parabolic trough (PT) systems are the most mature technologies used for CSP generation [15,17,20,21]. This is the reason that the PT plants are widely commercialized compared to other configurations of CSP [15].…”
Section: Parabolic Trough Systemsmentioning
confidence: 99%
“…CSP is a very well-tested and mature solar power plant designed for CSP [16,17,20] as shown in Figure 3. This is why in comparison to other CSP configurations, PT plants are more commonly commercialized [17].…”
Section: Parabolic Trough Systems the Parabolic Trough (Pt)mentioning
confidence: 99%
“…The system configuration is 10 modules per string with a DC-to-AC ratio of 1.2. PV modules have a 25- 20 International Journal of Photoenergy year life expectancy, with a 0.5 percent annual deterioration factor, while the inverter's life expectancy is set at 15 years.…”
Section: Selected System Details and Componentsmentioning
confidence: 99%
“…Their results showed that an optimal combination of SM and TES hours could reduce electricity cost by about 70%. Soomro et al [30] used the SAM software to present a performance improvement of cost-reduction analysis for a 50 MWe PT CSP plant for Abu Dhabi. It was concluded that an appropriate selection of the technology could reduce the cost, improve the system performance, and effectively meet energy demands.…”
Section: Introductionmentioning
confidence: 99%